On the influence of heterogeneity of graphene sheets in the determination of the pore size distribution of activated carbons - Alexandre de Oliveira, José Carlos (2011)
We model carbon-based microporous materials,such as activated carbons, taking into account surface defects in the form of geometrical rugosity in the inner surface of each graphitic slit pore. The used model is a simplified variation of the randomly etched graphite (REG) pore model (Seaton et al., 1997). When subcritical Ar or N2 is used as probe-gas to simulatethe adsorption process in slit pores assembled with ideally perfect graphene walls, the resulting pore size distribution (PSD) rather consistently shows a relatively low population of pores around 12?13 Å. This feature is supposed to be an artifact introduced by the perfect graphene sheets modeling assumptions. In this study, we particularly examine to which extent the gap of the PSD around 12?13 Å is linked to the perfect graphene sheet model and the effects of surface rugosity in the determination of the PSD. Adsorption isotherms of nitrogen at 77 K and local density distributions are studied simultaneously in the simulation. We found that, by mixing a complete series of heterogeneous pores with 25% of repulsive sites, a noticeable improvement in the fitting between the theoretical and the experimental isotherms was achieved and the PSD gap was eliminated. The mixed model with 25% of repulsive sites provided a more realistic estimate of the internal structure of microporous carbons.